An overview of organizational neuroscience - Ward, Mary; Volk, S.; Becker, W. (2015)
This chapter overviews organizational neuroscience (ON), covering the past, present, and future of this growing field of inquiry. First, we define ON and clarify the boundaries of the field. Second, we describe the evolution of ON by starting with early papers that tended to discuss the potential of ON to benefit both research and practice. Throughout its development, debates have abounded about the value of ON. Such debates are often related to challenges in collecting, integrating, interpreting, and using information from the brain-level of analysis. It is time for the field to move beyond these debates to focus on applying neuroscience to further theory development and reveal more comprehensive answers to research questions of importance to both academics and practitioners. Third, we propose and describe future research directions for ON. The research directions that we propose are merely a sample of the many paths along which ON inquiry can move forward. Fourth, we outline potential practical implications of ON, including: training and development, job design, high-performance assessment, motivating communications, and conflict prevention. Finally, we draw conclusions about ON as it stands today, address challenges in developing ON, and point out opportunities. We conclude with takeaways and highlight the importance of ON for both academics and practitioners.